Striking the right chord with organ donation - Ramaseshan, Balasubramani; Wong, David; Turner, Bradley (American Marketing Association, 2011)
This paper presents a social marketing framework for the promotion of organ donation. The framework considers self-interest (egotistic attitudes) and giving out of the goodness of your heart (altruistic attitudes) to be drivers of willingness to become an organ donor. The mediating effects of financial and non-financial incentives on willingness to donate are also included in the framework. With the division of motivational attitudes (egotistic and altruistic) and the adjunct effect of incentives, this paper gives policy makers fresh insight to the nature of the problem and offers some practical steps forward.